Physico-mechanical properties of buluh minyak (Bambusa vulgaris) particle board bonded with different solid content and resin content of citric acid - Jermaine Allen Emparie (2024)
Oil Bamboo (Bambusa vulgaris) is versatile bamboo that is often used because of its potential in various applications. However, the data on the properties of citric acid bonded particleboard fabricated from oil bamboo is lacking. Therefore, this study aims to investigate the physical and mechanical properties of bamboo particleboard, bonded with different solid content, and resin content of citric acid. Solid content (60% and 70%); and ii) resin content (10%, 20%, and 30%). The boards were pressed using a hydraulic press with pressing temperature and time of 180oC and 10 minutes respectively. The determination of physical and mechanical properties of the samples was conducted in accordance with JIS A 5908:2003. Physical properties, including density, moisture content, thickness swelling (TS), and water absorption (WA), were examined. Additionally, mechanical properties such as Modulus of Elasticity (MOE), and Modulus of Rupture (MOR) were assessed. The results show that the solid content and resin content affect the physical and mechanical properties of the particleboard which changes the particleboard for the better. Similarly, the resin content increase of particle board more water resistant.